Comparative Analysis of Behaviorism and Cognitivism Theories in Islamic Religious Education Learning - Mutaqin, Dadang Zenal; Saripudin, Uus; Choiriyah, Irma; Wulandari, Fitri; Habibah, Siti Nurhasanah (El-Rusyd, 2025)
This study aims to analyze and compare the theories of behaviorism and cognitivism in the context of Islamic Religious Education (PAI) learning, and to identify their implications for classroom learning design and practice. The method used is a literature study with a qualitative approach, utilizing academic references, Quranic verses, and hadith to enrich the analysis. The findings indicate that behaviorism emphasizes repetition, habituation, and reinforcement, making it suitable for teaching basic religious practices such as prayer and Quran memorization. Meanwhile, cognitivism focuses on internal mental processes such as understanding, reasoning, and reflection, making it effective in teaching values, concepts, and critical thinking. Both theories contribute to improving PAI learning by offering different yet complementary strategies. Behaviorism supports the formation of discipline and routine, while cognitivism promotes deeper comprehension and meaningful engagement with Islamic teachings. The implication of this study is the need for balanced and adaptive teaching methods that consider both behavioral and cognitive aspects to achieve holistic religious education.